New Develop Small Scale Machine Of Non-Destructive Test (Ndt) For Composite Inspection - Radzi, Mohamad Akmal Ridzuan (Universiti Sains Malaysia, 2019)
There are many types of the non-destructive test (NDT) method and ultrasonic testing is the most common method used in composite inspection. The main purpose of the inspection is to detect the defect that occurs in the composite such as cracks, delamination, void and others. The common Ultrasonic NDT equipment is quite larger, expensive and the system is also complex. This research is conducted to develop a small scale of NDT machine with a simple system and able to operate immersion ultrasonic testing of the composite and obtain the same result as the current product. The water is used as a coupling medium for the sound beam to travel between the transducer and specimen. The new design of water tank also has been developed to make this product become more ergonomic. This small scale machine will operate in two axis which is x and y axis and there are 2 NEMA-17 stepper motor used on the axis and controlled by using Arduino Genuino Mega 2560 and Adafruit Motor Shield v2 as a microcontroller and a motor driver respectively. In the inspection process, a tranducer of Harisonic Ultrasonic from Olympus corporation with a frequency of 2.25 MHz is used and a pulser-receiver is from US Ultratex. The process of inspection will be considered done after the performance of the machine has been optimized by undergoes some analysis. The result of the specimen such as the location and size of a crack can be gained from the signal. The sample of the specimen that being tested fibre glass composite laminates (FGCL) with holes as an artificial defect. The suitable stepping mode of the stepper motor with the least vibration produced during operation is analyzed. The structural analysis also is done by using simulation in Solidwork software. Motion study is used to analyze the basic hand, arm and body movements of users as they use this machine.